Attitudes of patients with spondylarthritis or rheumatoid arthritis regarding biological treatment during COVID-19 pandemic: A multi-center, phone-based, cross-sectional study - Coskun Zateri,; Murat Birtane,; İlknur Aktaş,; Selda Sarıkaya,; Aylin Rezvani,; Lale Altan,; Nigar Dursun,; Erbil Dursun,; Nurettin Taştekin,; Reyhan Çeliker,; Şenay Özdolap,; Kenan Akgün, (Archives of Rheumatology, 2021)
Objectives: In this study, we aimed to investigate the medical treatment attitudes of patients with spondylarthritis or rheumatoid arthritis (RA) who were using biological drugs during the novel coronavirus-2019 (COVID-19) pandemic. Patients and methods: In this multi-center, cross-sectional study, a total of 277 patients (178 males, 99 females; median age: 45 years; range, 20 to 77 years) who were using biological disease-modifying anti-rheumatic drugs (bDMARDs) for rheumatic diseases and were reached by phone between June 1st, 2020 and June 30th, 2020 were included. Demographic characteristics, working status, type of the rheumatic disease, comorbidities, smoking habits, and type of the bDMARDs were recorded. Disease activity was evaluated using the Visual Analog Scale (VAS). The patients were asked whether they continued the treatment plan, as it was before or changed and, if changed, how they changed the plan and what happened after the change. Results: Of the patients, 229 had spondylarthritis and 48 had RA. A total of 36.1% of the patients were smokers, and the most common comorbidity was hypertension (17.3%). Totally, 5.8% of the patients had a history of contact with a COVID-19 positive person. Only three (1.1%) patients were diagnosed with COVID-19 infection and none of them died. Of the patients, 64.3% continued their treatment, while 35.7% adopted various changes. Most patients made the decision about the treatment plan on their own (n=160, 57.8%), while 38.3% of them consulted their physicians and 13.9% of them consulted any health staff. The only significant parameter for changing the drug course was receiving intravenous bDMARDs (by infusion at hospital) (p=0.001). These patients had also a higher disease activity as measured by VAS, compared to the patients receiving non-infusion therapy (p=0.021). As a result of these changes, severity of the symptoms increased in 91 (32.9%) patients. Disruption of regular biological treatment and prior infusion therapy more likely worsened the complaints (p<0.001 and p=0.024, respectively). Conclusion: Intravenous bDMARD therapy seems to be the main factor affecting the continuity of the treatment in the pandemic period. During the pandemic period, alternative treatment options should be considered other than infusion therapy not to interrupt the treatment of these patients.